A Validation Study of Women’s Reports and Recalls of Major Complications Treated at Lampung Province, Indonesia - Ika Fitria Elmeida (International Journal of Health and Medicine, 2025)
The leading causes of maternal mortality are thought to include hemorrhage, sepsis, obstructed labor, and hypertensive disease of pregnancy. For many years, demographic and health surveys have been used to study maternal and perinatal health in developing countries. However, few nationwide population surveys have used formally validated questionnaires. Objectives: The purpose of this study was to determine the validity of maternal self-reports of obstetrical complications. Methods: A cross-sectional study was conducted among 300 women at Two Hospitals and one public health center. A questionnaire recorded mothers’ perceptions of obstetrical complications while hospital medical records. Sensitivity, specificity, predictive values, and percent agreement were obtained for obstetrical conditions. Result: In general, women’s reports of obstetrical complications did not match medical diagnoses. The highest agreement was obtained for reporting eclampsia, with less agreement for postpartum haemorrhage. Conclusion: The validity of the survey questionnaires varies between studies due to differences in the questionnaires. Health surveys based on maternal self-report must be interpreted with consideration of this limitation.